Brilliant cresyl blue staining does not present cytotoxic effects on human luteinized follicular cells, according to gene/protein expression, as well as to cytotoxicity tests - Alcoba, Diego Duarte; Capp, Edison (Reproductive biology, 2017)
In vitro oocyte maturation presents many advantages and its success is related to the selection of fully grown oocytes. In animal models, staining of cumulus-oocyte complexes (COCs) with Brilliant Cresyl Blue (BCB) is widely used for this selection. However, a lack of information about the safety of BCB makes its applicability in humans questionable. Because granulosa and cumulus cells have a close relationship with the oocyte and taking into account that follicular cells are also exposed to BCB when this pre-selection method is applied, we aimed to evaluate the effects of BCB on human follicular cells exposed to BCB. Cytotoxicity tests (Sulforhodamine B and Neutral Red Uptake) and gene and protein expression of elements related to the cell cycle (BAX, BCL2, TP53 and CDKN1A), as well as to cell death and metabolism (GAPDH), glucose consumption, and estradiol and progesterone secretion, were examined in granulosa and cumulus cells with and without exposure to BCB. Regardless estradiol secretion and glucose consumption, all other evaluations presented similar results between control and treated (BCB) groups, independently of cell type. Therefore, our results demonstrate convincingly that BCB seems to be safe for use in humans and it should encourage future studies to evaluate the development of embryos derived from human oocytes selected by BCB staining.
Gesehen am 20.04.2018